An Overview of the Grapefruit Market in France - Yan Heng; Mitzey Tejeda; Lisa House (EDIS)
The authors of this 4-page fact sheet, Yan Heng, Mitzey Tejeda, and Lisa House, used a national survey to analyze and understand French consumer preferences and consumption behavior regarding grapefruit. They found that more than half of the respondents were willing to purchase grapefruit in the upcoming year, suggesting that French consumers hold an overall positive image of grapefruit. As a major and well-recognized supplier providing high-quality products, Florida has the opportunity to continue producing and exporting grapefruit to France. Published by the UF/IFAS Food and Resource Economics Department. https://edis.ifas.ufl.edu/fe1072